2021
DOI: 10.3390/life11010039
|View full text |Cite
|
Sign up to set email alerts
|

LDL-Cholesterol and Platelets: Insights into Their Interactions in Atherosclerosis

Abstract: Atherosclerosis and its complications, including acute coronary syndromes, are the major cause of death worldwide. The two most important pathophysiological mechanisms underlying atherosclerosis include increased platelet activation and increased low-density lipoproteins (LDL) concentration. In contrast to LDL, oxidized (ox)-LDL have direct pro-thrombotic properties by functional interactions with platelets, leading to platelet activation and favoring thrombus formation. In this review, we summarize the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 84 publications
2
36
0
5
Order By: Relevance
“…Platelet activation in hypercholesterolemic states occurs through several mechanisms, including: (i) scavenger receptor cluster of differentiation (CD)36, (ii) scavenger receptor lectin-like ox-LDL receptor-1 (LOX-1), and (iii) LDL-C triggered platelet membrane composition changes [ 34 ]. The mechanisms of platelet activation by LDL are shown in Figure 2 .…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Platelet activation in hypercholesterolemic states occurs through several mechanisms, including: (i) scavenger receptor cluster of differentiation (CD)36, (ii) scavenger receptor lectin-like ox-LDL receptor-1 (LOX-1), and (iii) LDL-C triggered platelet membrane composition changes [ 34 ]. The mechanisms of platelet activation by LDL are shown in Figure 2 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…It is a ligand for a number of particles, such as thrombospondin-1, ox-LDL, fatty acids, microbial diacyloglycerides, and many others [ 35 , 37 , 38 ]. Previous studies have shown that the interaction of CD36 with ox-LDL triggers signaling pathways that activate platelets, inducing the expression of P-selectin and the activation of integrin α IIb β 3 (the receptor for fibrinogen), therefore facilitating the formation of platelet–leukocyte complexes via P-selectin and the cross-linking of adjacent platelets via fibrinogen [ 34 , 39 ]. The ox-LDL–CD36 interaction was shown to trigger platelet hyperreactivity via Src family kinases, Vav-guanine nucleotide exchange factors, cyclic guanosine monophosphate (cGMP), and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, producing reactive forms of oxygen and leading to a vicious circle of LDL oxidation and platelet activation [ 40 , 41 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of a specific treatment, it is crucial to establish the effect of co-administered medications in patients with COVID-19. Among cardiovascular medications, statins play a crucial role both in primary and secondary prevention of cardiovascular events [ 14 ]. Moreover, statins have well-established pleiotropic effects, including improvement of endothelial dysfunction, antioxidant properties, atherosclerotic plaque stabilization, and inhibition of inflammatory responses [ 14 ].…”
Section: Introductionmentioning
confidence: 99%